The Role of Sustainable Conservation Ecotourism in Agam Regency on Fishermen's Economic Income - Marhenna Uzra; Irwandi Irwandi; Suparno Suparno; Siti Aisyah (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
In accordance with Minister of Maritime Affairs and Fisheries Regulation Number 31 of 2020, the Zoning Plan for marine conservation areas is structured based on function by considering resource potential, carrying capacity and ecological processes. The aim of this research is to identify and analyze the role of conservation and sustainable ecotourism in Agam Regency on the economic income of fishermen. The research method used is quantitative descriptive. Primary data and secondary data come from fishing communities and related agencies. Collecting physical data by diving using diving equipment and developing analysis using SWOT analysis. The results of the research showed that the role of conservation really opens up economic opportunities for the income of fishermen in Agam Regency. There are areas that fishermen can use as a source of livelihood to meet fishermen's living needs in a sustainable manner, such as opening areas for marine tourism. The SO strategy obtained with a value of 5.19 is a conservation policy that regulates the management of coastal areas to be developed into integrated tourism visiting areas by exploiting existing potential. Increasing supporting facilities and capacity for tourists by utilizing communication technology and social media.